Komparatif Penanganan Konflik Hubungan Perjanjian Kredit Secara Hukum Perdata dan Hukum Islam - Ade Oktariatas KY (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
Form of agreement in Indonesia define two concepts are based on the National Civil Law and is based on Islamic law. The National Civil Law resources implementation agreement sets in Indonesia, by Privat Law Codifiation Book (Kitab Undang-Undang Hukum Perdata) whereas, implementation of the agreement is based on Islamic law source of Islamic Law Al- Qur'an, Sunnah and Ijtihad. The Indonesian government facilitate people to choose the law to make an agreement based on the two concepts rules in accordance with the needs and benefit profitable. The example form of the agreement is a credit agreement at Conventional Banking and Islamic Banking in Indonesia. Legal issues studied in this paper is how the legal position of the credit agreement in the civil law and Islamic law in Indonesia, as well as how the dispute settlement mechanism of credit agreement with civil law and Islamic law on a case study of Conventional and Islamic Banking in Indonesia. Methods of research in this paper uses normative legal approach to analyzing the applicable laws are translated literature study. The results of this paper describes form the legal position of the credit agreement, and the dispute settlement mechanism of the agreement by national civil law and sharia.